Multiple tissues express alpha 1-antitrypsin in transgenic mice and man. - Carlson, J A (1988)
Hepatocytes are considered to be the predominant source of alpha 1-antitrypsin (AAT), the major antiprotease in human plasma. The development of emphysema in the hereditary PiZ AAT deficiency state suggests that inhibition of leukocyte elastase in the lung is a major function of this protein. In addition, patients with AAT deficiency are at increased risk for developing cholestasis in infancy and chronic liver disease as adults. The mechanism for hepatic cell injury, however, is not understood. Transgenic mice that express the normal human AAT gene demonstrate abundant AAT in hepatocytes and specific cell types of numerous nonhepatic tissues. Immunoperoxidase techniques have previously disclosed AAT in many of the cell types seen in transgenic mice; however, the issue of local synthesis vs. endocytosis in these cell types has remained unresolved. In this study, AAT mRNA was seen in a variety of tissues in the transgenic mouse. Immunoelectron microscopy of renal tubular and small intestinal epithelial cells in the transgenic mice demonstrated AAT within the cisternae of the rough endoplasmic reticulum, as in hepatocytes. These findings support the possibility of local synthesis in the various cell types. The results suggest that in addition to maintaining tissue integrity in the lung, the protease/antiprotease balance may have physiological functions in other organs as well.